Monochorionic Diamniotic Twins with Sex Discordance: Case Series - Valentina Sala; Luigina Spaccini; Stefano Faiola; Daniela Casati; Arianna Laoreti; Lisanne S. A. Tollenaar; Enrico Lopriore; Mariano M. Lanna (Diagnostics)
Background and Clinical Significance: Ultrasonographic diagnosis of twin pregnancies has become routine, with chorionicity playing a crucial role in assessing associated risks. Traditionally, monochorionic (MC) twins were believed to derive from a single zygote, ensuring sex concordance. However, recent cases of dizygotic monochorionic (MCDZ) twins challenge this paradigm. In this paper, four cases of MCDZ twins with sex discordance are described. Case presentation: Case 1 and case 2 describe two spontaneous MC/diamniotic twin pregnancies in which sex discordance between twins was attributed to blood chimerism. Case 3 is about a MC/diamniotic twin pregnancy derived from a single blastocyst transfer after in vitro fertilization (IVF), and that was complicated by twin-to-twin transfusion syndrome, with zygosity testing confirming the dizygosity. Case 4 is a twin anemia polycythemia sequence diagnosed after birth in twins considered dichorionic during pregnancy (due to sex difference) and defined as monochorionic after placental examination. Conclusions: The prevalence of monochorionic dizygotic (MCDZ) twins remains uncertain, and many cases likely go unnoticed, particularly when twins are of the same sex. In twin pregnancies, determining chorionicity during the first-trimester ultrasound (US) is critical. Accurate identification of monochorionicity is essential for managing potential complications. Careful verification of sex concordance between twins is necessary. In cases of sex discordance, amniocentesis is required for karyotype evaluation and zygosity testing.